2016
DOI: 10.1007/s00262-016-1914-6
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and evidence to combine radiation therapy and immunotherapy for cancer treatment

Abstract: Cancer immunotherapy exploits the immune system's ability to differentiate between tumor target cells and host cells. Except for limited success against a few tumor types, most immunotherapies have not achieved the desired clinical efficacy until recently. The field of cancer immunotherapy has flourished with a variety of new agents for clinical use, and remarkable progress has been made in the design of effective immunotherapeutic regimens. Furthermore, the therapeutic outcome of these novel agents is enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…Our knowledge on RIBEs derives mostly from preclinical studies. The RIAE and RIBE do however exist, as demonstrated here, and they can be intentionally induced by radiation, leading to partial and/or complete long lasting regression of metastatic disease [19]. It is still unclear why these non-targeted effects have only been seen sporadically until now.…”
Section: Discussionmentioning
confidence: 84%
“…Our knowledge on RIBEs derives mostly from preclinical studies. The RIAE and RIBE do however exist, as demonstrated here, and they can be intentionally induced by radiation, leading to partial and/or complete long lasting regression of metastatic disease [19]. It is still unclear why these non-targeted effects have only been seen sporadically until now.…”
Section: Discussionmentioning
confidence: 84%
“…Irradiation has multiple inhibitory and stimulatory effects on the immune system such as increased CD4 + , CD8 + and Treg Cells infiltration into TME [3,4] Some regimens of radiation like ablative RT was associated with increased infiltration of exhausted CD8+ T cells into the tumor, which induced radiation resistance. [5,6]. The combination of radiotherapy and Immune checkpoint blockers therapy can reduce these inhibitory effects by stimulating immune cells and enhancing the response to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have shown that the combination of RT with ICIs is more effective than either treatment modality alone. [22][23][24][25][26][27] Despite the hype, such treatment combinations are still far from standard clinical practice, because the optimal timing, dosing, and fractionation of RT to yield the best synergistic outcomes remain uncertain. Moreover, data on the safety of such combinations are scarce.…”
Section: Introductionmentioning
confidence: 99%